The Right To Time For Worship: International Conventions And The Practice In England, America And Nigeria - Oba, A.A. (Journal of Malaysian and Comparative Law, 2001)
This article highlights the principal international conventions on the right to freedom of religion with particular reference to the right to an adequate period for worship and examines the practice in some selected countries, namely, Britain, America and Nigeria.